0-categorical structures with a predimension - Evans,DM (Annals of Pure and Applied Logic, 2002)
We give an axiomatic framework for the non-modular simple 0-categorical structures constructed by Hrushovski. This allows us to verify some of their properties (weak elimination of imaginaries, simplicity, the nature of forking, CM-triviality and stable forking) in a uniform way, and to show that these properties are preserved by iterations of the construction. © 2002 Elsevier Science B.V. All rights reserved.